Perancangan Produk Interior Bidang Kerja Home Office Multi Feature Dengan Pendekatan Ergonomi - Dominique Glenn Leonardo; Grace Mulyono; Frenky Tanaya (Intra, 2018)
With the rapid growth of technology in this modern era, the needs of human being as a working individual that interact with each other also expanding. The needs of technology are crucial to help and support daily activities and work activities as well. Those needs also generate new habits and trigger the necessity of Interior product that able to support and ease the user’s activities, especially when working at their home office. Based on those needs, also lack of particular product in the market, an innovative working table for home office will be designed based on the ergonomic aspect and several features that will support and give the best experience in comfort for its users. Moreover, it will also provides versatility and freedom in using the table either by sitting or standing.